Estratégia de seleção de linhagens de arroz de terras altas para qualidade dos grãos - Silva, Camila Soares Cardoso da (2019)
The joint evaluation of all characteristics related to grain quality in a breeding program has fundamental importance for the best selection of lines. However, this is a difficult process due to the natural complexity of these characters and the number of components to be worked on. In this sense, the aim in this study was to evaluate the characteristics of the industrial, physical, chemical and culinary quality of upland rice grains, identifying a smaller number of factors that represent the number of characters evaluated to verify later the existence of a main character of grain quality. This character may be used in the indirect selection of other important traits and assist in the selection of genotypes with desirable quality in the grains in the initial stages of breeding programs. Twenty four genotypes and three control cultivars belonging to the VCU (Value for Cultivation and Use) assay of UFLA highland rice breeding program in partnership with Embrapa Rice and Beans and EPAMIG were evaluated. The experiments were conducted in Lavras-MG, Lambari-MG and Registro-SP in the crop year of 2016/17 and 2017/18. The experimental design used was the randomized block design with three replications and plots consisted of five rows, and each row had four meters. The following characteristics were evaluated: milling grains (MG), hulling grains (HG), chalkiness (CH), L/B ratio (LB), amylose content (AC), gelatinization temperature (GT), cooking time (CT), instrumental texture analysis (ITA), water absortion index (WAI), and volume expansion coefficient (VEC). With the measured values, were obtained the joint analysis and the principal component analysis for all the characters. Afterwards, phenotypic correlations and the path analysis of the characters that stood out most in the PCA was carried out. It was concluded that the characters of industrial, physical, chemical and culinary quality of the grains were differentiated into six distinct groups in which the breeder should concentrate the selection. LB, WAI and GC act independently, and the breeder should perform the direct selection in order to obtain genetic gains for such characters. AC and GT are highly associated, being able to use one of these characters for indirect selection in the other.